Carbon Tax Burdens on Low-Income Households: A Reason for Delaying Climate Policy? - Ian Parry (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper discusses techniques for measuring the incidence of carbon taxes across different household income groups and provides some cross-country estimates of these effects for selected advanced countries. The general message of this paper is that distributional concerns should not necessarily hold up carbon pricing. Energy price impacts may be less regressive than often supposed and there are ample opportunities in advanced countries for adjusting tax and benefit schedules to alter the overall incidence of a carbon tax reform. Insofar as possible however, using carbon tax revenues in ways that enhance economic efficiency is critical for containing overall costs to the economy.
Keywords: H22; Q52; Q54; Q58; 330; carbon tax; distributional incidence; fiscal reform; climate change; revenue recycling